The Influence of Transactional Leadership on Innovative Work Behavior and Its Impact on Employee Performance - Ummi Wahyuni; Fathorrahman Fathorrahman; Zainurrafiqi Zainurrafiqi; Nurul Hidayati (Pusat Riset dan Inovasi Nasional, 2024)
The dynamic development of Indonesia's industrial sector has prompted companies to focus on enhancing employee performance through effective leadership strategies. One of the leadership styles widely implemented in organizations is transactional leadership, which emphasizes clear structures, rewards, and supervision. However, its influence on innovative work behavior and employee performance in the context of manufacturing remains underexplored. This study aims to investigate the influence of transactional leadership on innovative work behavior and examine how this behavior subsequently affects employee performance at PT. Konveksi Jaya, a garment manufacturing company in Pamekasan. A quantitative approach was applied through a structured survey method, involving 80 employees selected using purposive sampling techniques. Data were collected using standardized questionnaires and analyzed using regression analysis to determine the strength and significance of the relationships among variables. The results reveal that transactional leadership positively influences innovative work behavior, and in turn, this innovative behavior significantly contributes to improved employee performance. The synthesis of these findings suggests that fostering a transactional leadership style that actively supports innovation can enhance overall employee effectiveness. The study concludes that while transactional leadership is often associated with routine performance, its role in promoting innovation is equally crucial, especially when appropriately aligned with employee needs and organizational goals. These insights are valuable for organizational leaders aiming to balance structure and innovation to drive sustainable employee performance.